TINGKAT KEPUASAN AUDITI INSPEKTORAT JENDERAL KEMENTERIAN PERTANIAN - Winniasri, Evy Fachraini (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2014)
Level of Auditee Satisfaction is important for the Inspectorate General of the Ministry of Agriculture, in order to identify the weakness of each dimension in delivering internal controlling activity and to determine the performance of internal controlling system in the Ministry of Agriculture. The objectives of this study are to analyze auditee satisfaction of internal control held by Inspectorate, to determine factors influencing auditee satisfaction, and to formulate strategies in increasing auditee satisfaction. Service Quality model was used to measure the perception of vertical institution under the authority of the Ministry of Agriculture on services received from Inspectorate. There were five dimensions that were measured, i.e tangibility, reliability, assurance, responsiveness, and empathy. Data were collected from 193 respondents. The study used Structural Equation Modelling (SEM) and software LISREL for data processing. The result reflected that all variables were significantly correlated to each dimension of Service Quality instrument and significantly influenced auditee satisfaction. Satisfactions were measured through overall satisfaction, the function of internal control related with non audit activity and the quality of audit report. Tangibility was the most significant factor influencing auditee satisfaction.